Effect of CO2 Exposure on the Chemical Stability and Mechanical Properties of BaZrO3‐Ceramics. Issue 11 (28th July 2016) - Sažinas, Rokas; Bernuy‐López, Carlos; Einarsrud, Mari‐Ann; Grande, Tor
Abstract : The reactivity of BaZrO3 with CO2 has been addressed as one of the major challenges with BaZrO3 ‐based electrolytes in protonic ceramic fuel cells. Here, we present a study of the effect of CO2 exposure on BaZrO3 ‐materials at elevated temperatures. Dense BaZr1− x Y x O3− x /2 ( x = 0, 0.05, 0.1, 0.2) and BaCe0.2 Zr0.7 Y0.1 O2.95 ceramics were prepared by sintering of powder prepared by spray pyrolysis. The Vickers indentation method was used to determine the hardness and estimate the fracture toughness of pristine materials as well as the corresponding materials exposed to CO2 . Formation of BaCO3 on the surface of exposed ceramics was confirmed by X‐ray diffraction and electron microcopy. The reaction resulted in formation of Ba‐deficient perovskite at the exposed surface. The reaction with CO2 was most pronounced at 650°C compared to the other temperatures applied in the study. The reactivity was also shown to depend on the Y‐content and the grain size and was most pronounced for BaZr0.9 Y0.1 O2.95 . The reaction with CO2 was observed to have a profound effect on the fracture toughness of the ceramics, demonstrating a depression of the mechanical stability of the materials. The results are discussed with respect to the chemical and mechanical stability of BaZrO3 materials, with particular emphasis on the composition and grain size.